CHANGING THE PARADIGM OF SCIENTIFIC WRITING IS DIFFICULT WITH THE TPACK LEARNING FRAMEWORK - Khairun Nisa; Syahrul R; Haris Effendi Thahar (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
In the era of digital society 5.0, it offers much technology to help students write. However, the available technology will not be used by students if it has not been introduced and taught to use technology that can be used in writing scientific papers. Lecturers can use the TPACK learning framework to teach and train students to write scientific papers. This research belongs to survey research. This study looked at the responses of 40 students taught using technology in applications or recommended websites to facilitate writing scientific papers. The research instrument is in the form of a questionnaire that includes the four components of TPACK based on the recommended technology. The findings showed that the TPACK learning framework could change students' mindsets in writing scientific papers to be easier and more enjoyable. After introducing and teaching techniques with the stages of the TPACK learning framework that can be utilized, students are interested and find it helpful in finding the latest research ideas/topics with many easily accessible references: Publish or Perish, paraphrasing citations from articles to avoid plagiarism: Smoodin, improving writing and grammar: google document and using the reference manager application to help create an automated bibliography: Mendeley.